Civil society’s communicative agency in strengthening community participation for environmental care in Cisayong - Bakti, Iriana; Sjuchro, Dian Wardiana; Faustine, Peace (Universitas Padjadjaran, 2025)
Background: The value of environmental awareness in rural communities has increased in recent years, particularly in areas where traditional customs intersect with contemporary ecological concerns. It is evident in the Indonesian village of Cisayong, located in southern West Java. Purpose: This article employed Giddens’ framework to show how civil society promoted environmental awareness in the village. Methods: This research was conducted through observation, FGDs, and in-depth interviews with local leaders in Cisayong Village. Results: The research indicated that civil society emerges from community, religious, and youth leaders who collectively embrace the environment. Moreover, each of these civil societies has effectively communicated messages about environmental awareness and garnered recognition from the village government for their efforts. Conclusion: The village community exhibits distinctive socio-cultural and economic characteristics that limit its ability to address environmental challenges effectively. However, through the initiative of local leaders, these limitations have become opportunities for developing community-based environmental awareness rooted in religion and culture. Implication: This finding suggested the empowerment of local actors as agents of change to build environmentally conscious social structures. Strengthening these initiatives can improve long-term environmental resilience in similar rural contexts.